MENGGALI DAN MENGAMBARKAN POTENSI KREATIVITAS SENI PADA ANAK USIA DINI - Zahra, Firza Hardyn Aira; Faisal, Vava Imam Agus (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
The presence of young children in dance activities is growing rapidly. This can be seen both in formal and non-formal education. However, what is very worrying is that there is no difference in the material presented between adults and children, so that what is presented is not optimal. This happens because the songs or dance movements that are performed do not match the child's level of ability, for example the child's voice or movement area is in accordance with the capacity of the anatomical structure, so what the couple wants to convey is not communicative. To overcome these obstacles, it is necessary to develop creative potential starting from an early age. It can be ensured that if children have been sharpened and cared for from an early age to maximize their potential movement abilities, a number of professional dancers will be born who in turn will become functional dancers. To overcome the above phenomenon, concern from various parties is needed, for example choreographers must produce dances that are appropriate to the level of difficulty of the movements achieved by the children. Art artists who act as instructors must consider materials that are appropriate to children's worlds so that they can display them more smoothly and flexibly. On the other hand, the concern of art observers such as the Cultural Park and the Arts Council is also very much needed in order to provide motivation and control to maintain the quality of the bank of songs or art movements displayed.